2022
DOI: 10.21608/ejhm.2022.260743
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of First Trimester Uterine Artery Doppler, Placental Growth Factor and Maternal Characteristics in Prediction of Preeclampsia

Abstract: Background: Preeclampsia is a major contributor of maternal and perinatal morbidity and mortality. The purpose of this study was to look at the predictive usefulness of placental growth factor (PLGF), maternal characteristics (MC), and uterine artery Doppler for preeclampsia in the first trimester. Patients and methods: A cross-sectional survey was conducted on 805 pregnant women between 11 + 0 and 13 + 6 weeks' gestation. A complete history and clinical examination were taken at the booking visit, a bilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…In this study, females with preeclampsia have statistically significant lower PlGF than females without preeclampsia. This is in accordance with Negm et al [10] who reported that, Patients with PE had reduced maternal PLGF levels than women in the control group when the study groups' levels were examined. This is consistent with Mosimann et al [12] , who investigated the value of repeating first trimester PLGF in PE screening as well as the importance of timing it.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, females with preeclampsia have statistically significant lower PlGF than females without preeclampsia. This is in accordance with Negm et al [10] who reported that, Patients with PE had reduced maternal PLGF levels than women in the control group when the study groups' levels were examined. This is consistent with Mosimann et al [12] , who investigated the value of repeating first trimester PLGF in PE screening as well as the importance of timing it.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding parity and the method of labour, there was no significant difference in this study between the preeclamptic and non-preeclamptic females. This agrees with Negm et al [10] He said that there were no significant differences in mean number of deliveries or parity between the research's examined groups. This contradicts the results of Kashanian et al [11] who examined the risk factors for preeclampsia and found that having more than one child is a significant protective factor against preeclampsia.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation